Effect of Blood Pressure on the lipids and Percentage of Fatty Acids of Blood Serum - Jasim, Mohammed A.H.; JalalAldin, Shaymaa Z. (International Journal of Psychosocial Rehabilitation, 2020)
This study included (50) samples of high blood pressure males and females with ages between between(80-19) years and (50) samples of healthy people who are not infected with any apparent disease males and females were considered a control group of the same categories Age above. In this study, blood samples were collected for healthy people in the case of fasting and control group period for fasting group then the serum was separated, where the serum divided into two parts .The biochemical parameters in part one glucose(Glu), total cholesterol(TC), high-density lipoprotein cholesterol(HDL), low-density lipoprotein cholesterol(LDL),very low-density lipoprotein cholesterol(VLDL), triglyceride(TG) and phospholipids was measured by using kits obtained from regional and international suppliers.the measurement of percentage of fatty acids in the three parts (CE, TG, PL) was performed by Capillary Gas Chromatography (CGC). The results showed that there was a significant increase in the percentage and level of saturated fatty acids (SFA), a significant decrease in monounsaturated fatty acids (MUFA) and a significant decrease in polyunsaturated fatty acids (PUFA), in the cholesterol ester (CE) part of serum lipids for the fasting group compared with the control group.Also, the results of this study showed that there was a significant increase in (SFA), a significant decrease in (MUFA), and a significant increase in (PUFA) in triglyceride (TG) part in serum of the fasting group compared to the control group.The results showed that there was a significant increase in (SFA), a significant decrease in (MUFA) and a significant decrease in (PUFA) in phospholipids (PL) part in the serum for the hypertension group compared with the control group.